Literature Study Review Of Vaccine Development Against African Swine Fever (ASF) - Gregorius Ronaldo Mau Kuru; Yohanes T.R.M.R Simarmata; Maxs U.E Sanam (Jurnal Veteriner Nusantara, 2022)
Pig is one of the livestock commodities that is used to fulfill animal protein needs because it has a high percentage of carcass. In pig farming industrial, there are various problems, one of which is African Swine Fever which is very infectious and can cause sudden death on a large scale in an endemic area. Various efforts have been made, one of which is developing a vaccine against African Swine Fever. Vaccines are antigens in the form of microorganisms that are dead, still alive but attenuated, still intact or parts of which have been processed, in the form of toxin microorganisms that have been processed into toxoids, recombinant proteins. This literature review aims to determine the development and effectiveness of vaccines in controlling the incidence of African Swine Fever. This literature study was obtained from searching and collecting from various reference sources using the Mendeley and Google Scholar applications. Based on a review of literature studies with literature, it was found that until now no vaccine has been found that can induce the formation of antibodies against African Swine Fever, but the type of vaccine is a live attenuated virus which has enormous potential to be developed into a vaccine because it is able to provide protection against homologous virus strains but still being developed to be able to provide cross-protection against heterologous viral strains.